2024
DOI: 10.1038/s44220-024-00259-5
|View full text |Cite|
|
Sign up to set email alerts
|

Early detection of dementia with default-mode network effective connectivity

Sam Ereira,
Sheena Waters,
Adeel Razi
et al.

Abstract: Altered functional connectivity precedes structural brain changes and symptoms in dementia. Alzheimer’s disease is the largest contributor to dementia at the population level, and disrupts functional connectivity in the brain’s default-mode network (DMN). We investigated whether a neurobiological model of DMN effective connectivity could predict a future dementia diagnosis at the single-participant level. We applied spectral dynamic causal modeling to resting-state functional magnetic resonance imaging data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Here, we showed that effective connectivity parameters related to group differences were helpful in predicting group membership. These results align with a recent study showing that resting-state DMN effective connectivity can predict dementia incidences before disease-onset in a relatively larger sample 47 , which supports the clinical usefulness of DMN effective connectivity in neurodegenerative disorders.…”
Section: Predicting Group Membership and Cognitive Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we showed that effective connectivity parameters related to group differences were helpful in predicting group membership. These results align with a recent study showing that resting-state DMN effective connectivity can predict dementia incidences before disease-onset in a relatively larger sample 47 , which supports the clinical usefulness of DMN effective connectivity in neurodegenerative disorders.…”
Section: Predicting Group Membership and Cognitive Performancesupporting
confidence: 91%
“…The groups showed a mixed pattern of excitatory and inhibitory connections within DMN. However, outgoing connections from HPC to other DMN regions were inhibitory across all groups, while interhemispheric HPC connections were excitatory, which is in line with a recent study investigating effective connectivity in healthy elderly and demented patients 47 . Missing entries correspond to redundant connections that have been removed following Bayesian model reduction (that did not differ from their prior expectation).…”
Section: Group Meanssupporting
confidence: 90%